REPRESENTATION OF RACISM IN FILM (STUDY OF SEMIOTICS OF RASISM IN A GET OUT FILM - Emerald Surya JR (Jurnal Ilmiah Komunikasi Makna, 2021)
Through the film "Get Out", the message of racism is shown to demonstrate the evolving behavior of human racists. This film tells the story of a modern black experience named Cris who carried the history of his ancestors. The study was conducted to represent a form of racism, the study used a qualitative method with a descriptive approach, data was obtained by observing images and dialogue. Data analysis using Roland Barthes's semiotic model which consists of a signaling order, namely denotation and connotation. The primary data source is behavior between players, and the main character, secondary data obtained from the literature. The results showed that there were three forms, the first black prejudice to whites, both discrimination against blacks, and the third change in the value of black racism. From the story on "Get Out" film shows the behavior of racism still exists today, and is growing